ASI EKSKLUSIF PEMICU PERTUMBUHAN DAN PERKEMBANGAN MOTORIK BAYI DI PUSKESMAS BANDAR KHALIFAH - Juita Sari; Mestika Riza Helty; Suhartini (Jurnal Keperawatan Priority, 2021)
The problems faced today are that even though the government has long campaigned for exclusive breastfeeding, in practice the coverage rate is still low. The purpose of this study was to find out how exclusive breastfeeding affects the growth and development of infants, to prove the differences in growth and development of babies who are given exclusive breastfeeding and non-exclusive breastfeeding, and to find out how mothers practice exclusive breastfeeding. The research method used is an analytical method with a Quasi Experiment design. The population in the study were all mothers who had babies aged 6-12 months in the Bandar Khalifah Public Health Center. Samples were taken using accidental sampling techniques. Data obtained from respondents through interviews, evaluating the baby's record book, namely the Maternal and Child Health book or KMS, as well as observations made to see the baby's motor skills. Data analysis using statistical tests with comparative test analysis with the Mann Withney Test test tool. Result of the research There are significant differences in body weight growth, fine motor development, and gross motor development between exclusive breastfeeding and non-exclusive breastfeeding babies where the growth in body weight and development of babies who are exclusively breastfed is faster than that of babies who are not exclusively breastfed.